Identity and Belonging as Positionality. An Approach from Intersectionality - Arce-Cuadros, Claudia (2016)
In this article terms we may use to refer to identities and the meanings of belonging in a multicultural context are considered. For this purpose, we study Stuart Hall’s concept of vernacular cosmopolitism, which recognizes identities as points of suture between discourses and practices; that is, alignments between two scopes: a constitutive outside, and interiority produced by the self. On the other hand, we study the intersectionality approach, which considers that axes of social stratification are mutually organized and interconnected; therefore, identities are not built in relation to fixed groups such as class, ethnic group, nation, but as social positionalities letting the representation of multiple identities to operate simultaneously as possible.